Nitrogen metabolism and gas exchange parameters associated with zinc stress in tobacco expressing an ipt gene for cytokinin synthesis - Pavlíková, Daniela; Pavlík, Milan; Procházková, Dagmar; Zemanová, Veronika; Hnilička, František; Wilhelmová, Naďa (Journal of plant physiology, 2014)
Increased endogenous plant cytokinin (CK) content through transformation with an isopentyl transferase (ipt) gene has been associated with improved plant stress tolerance. The impact of zinc (tested levels Zn1=250, Zn2=500, Zn3=750mgkg(-1)soil) on gas exchange parameters (net photosynthetic rate, transpiration rate, stomatal conductance, intercellular CO2 concentration) and nitrogen utilization by plants resulted in changes of free amino acid concentrations (glutamic acid, glutamine, asparagine, aspartate, glycine, serine, cystein) and differed for transformed and non-transformed tobacco plants. For pot experiments, tobacco plants (Nicotiana tabacum L., cv. Wisconsin 38) transformed with a construct consisting of SAG12 promoter fused with the ipt gene for cytokinin synthesis (SAG plants) and its wild type (WT plants as a control) were used. Physiological analyses confirmed that SAG plants had improved zinc tolerance compared with the WT plants. The enhanced Zn tolerance of SAG plants was associated with the maintenance of accumulation of amino acids and with lower declines of photosynthetic and transpiration rates. In comparison to WT plants, SAG plants exposed to the highest Zn concentration accumulated lower concentrations of asparagine, which is a major metabolic product during senescence.
Keywords: aminokyseliny; Toxic element stress; fotosyntéza; Photosynthetic rate; Nitrogen; Photosynthesis; promotorové oblasti (genetika); rostlinné proteiny; Amino acid; Cytokinins; regulace genové exprese u rostlin; Senescence; cytokininy; Plants, Genetically Modified; Nicotiana; Gene Expression Regulation, Plant; Promoter Regions, Genetic; dusík; geneticky modifikované rostliny; zinek; Zinc; tabák; Amino Acids; Plant Proteins